TO THE SYSTEMATIZATION OF WEFT TUCK STRUKTURES - HOLOVNIA, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In this work is examined the influence of the spatial placement of the tuck half-stitch on the structure and properties of double weft knitted fabric. The detailing of the systematization of weft knitted tuck fabric to this feature is given on the examples of the specific tuck structures, including those developed by the author at the patent level. Three variants of spatial placement of the tuck half-stitch are considered: one-plane, two-plane and intermediate. In case of one-plane placement a tuck-stitch and loops connected with it are in the same structural layer. They are formed with one needle bed.  In case of two-plane placement a tuck-stitch connects the loops of the same layer in double weft tuck knitted fabric, and the tuck half-stitch itself is in the opposite layer. Loops connected by a two-plane tuck half-stitch and the tuck half-stitch itself are formed with different needle beds. The tuck half-stitch of intermediate placement (intermediate tuck half-stitch) connects the loops of different structural layers in double weft knitted fabric. Loops connected by an intermediate tuck half-stitch are formed with different needle beds. The intermediate tuck half-stitch is the most oriented along the loop row. Of the three options for spatial placement of the tuck half-stitch  the main attention is focused on the intermediate, as the least researched. Two double structures of weft knitted fabric with intermediate tuck-stitches are developed: double patterned half-cardigan and cardigan. On the example of developed double cardigan and double half-cardigan with intermediate tuck half-stitches are clarified the features of the interaction between loops and intermediate half-stitches and its influence on the structure and properties knitted fabric. The clarified role of intermediate tuck-stitches in preserving the width of double weft knitted fabric after the removal loop columns in it. The results of the work make it possible to carry out a more reasonable design of weft tuck knitted fabric and expand the range structures based on it.
Keywords: loop; tuck half-stitch; structure; interaction; needle; half-cardigan; cardigan